The Chinese variable in Saudi-Iranian relations (قضايا سياسية, 2024)
China's relations with the countries of the region have witnessed development in light of the growing development that relations between China and the countries of the Arabian Gulf region are undergoing within the new global framework. This framework is based on the establishment of a multipolar global system in which participation from emerging countries is necessary and important. Since Iran and Saudi Arabia announced In March 2023, their diplomatic relations severed since 2016 were resumed, after negotiations led by China. Arab and international reactions continued regarding the impact of this agreement and the dimension it carries with regard to China’s relations and influence in the region, as China considered the agreement a “victory for dialogue and a victory for peace,” emphasizing It will continue to play a constructive role in dealing with thorny issues in the world and will demonstrate its responsibility as a major power, which raised the concerns of the United States of America, especially since the mediation came in conjunction with tense relations between Iran and the West due to its nuclear file, and a Saudi desire to take more independent steps regarding its relations with... The United States and its foreign policy after the tension in their relations, especially in the oil and human rights issues.